On the origins and fate of chromosomal abnormalities in human preimplantation embryos: an unsolved riddle. (11th April 2022) - Regin, Marius; Spits, Claudia; Sermon, Karen
Abstract: About 8 out of 10 human embryos obtained in vitro harbour chromosomal abnormalities of either meiotic or mitotic origin. Abnormalities of mitotic origin lead to chromosomal mosaicism, a phenomenon that has sparked much debate lately as it confounds results obtained through preimplantation genetic testing for aneuploidy (PGT-A). PGT-A in itself is still highly debated, not only on the modalities of its execution but also on whether it should be offered to patients at all. We will focus on post-zygotic chromosomal abnormalities leading to mosaicism. First, we will summarize what is known about the rates of chromosomal abnormalities at different developmental stages. Next, based on the current understanding of the origin and cellular consequences of chromosomal abnormalities, which is largely based on studies on cancer cells and model organisms, we will offer a number of hypotheses on which mechanisms may be at work in early human development. Finally, and very briefly, we will touch upon the impact our current knowledge has on the practice of PGT-A. What is the level of abnormal cells that an embryo can tolerate before it loses its potential for full development? And is blastocyst biopsy as harmless as it seems?